Traumatic testimonies :|trauma, temporal hybridity, and language in The God of Small Things and Lolita - Oliveira, Cristiane Regina de. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Vladimir Nabokov's Lolita (1955) and Arundhati Roy's The God of Small Things (1997) narrate the traumatic effects of societal transgressions, namely pedophilia and incest. The authors distort literary notions of time and language by utilizing temporal hybridity and semiotic language in order to replicate the experience of abject trauma through fictional testimony. The novel's recurrence of certain words, events, and behaviors reinforce the repetitive nature and recall of trauma. The use of unusual and lyrical language, resulting in aesthetically beautiful novels, serve to ease both the characters and readers’ confrontation of the abject and forces them to reconsider societal ethics. Chapter 1 is an introduction to theoretical arguments on trauma, temporal hybridity, semiotics and the abject posited by Julia Kristeva, Cathy Caruth, Elizabeth Outka, and L. Chris Fox. Chapter 2 considers trauma and time, namely the characters' traumatic experiences and their impact on their perception of time and the novels' structure, which simulate the disorienting nature of a traumatic experience for the reader. Chapter 3 analyzes how trauma alters the characters' language, forcing them into a dialogue with the semiotic and the abject, and manipulating the reader into a complicity that challenges their morals. Chapter 4 offers a conclusion to the analyses elaborated in this work and argues that the authors' non-native command of English creates another dimension to the semiotic styles employed in elucidating trauma through fiction.
Keywords: Nabokov, Vladimir Vladimirovich, 1899-1977 -- Criticism and interpretation.; Child sexual abuse in literature.; Abjection in literature.; Pedophilia -- Drama.